Representation of the life of visual sensory disabilities in religious poetry: A semiotic study by Roland Barthes - Irfai Fathurohman; Luthfa Nugraheni; Muhammad Sholikhan; Riyan Dwi Cahyaningsih; Isna Fatkhur Rohmah (Universitas Dian Nuswantoro, 2026)
This study examines the representation of the life experiences of individuals with visual sensory disabilities in religious poetry through Roland Barthes’ semiotic framework. The research aims to identify (1) denotative meanings, (2) connotative meanings, and (3) myths embedded in the poems. This study employs a qualitative descriptive method with a narrative approach. Data were collected through observation, interviews, and documentation at the Pendowo Social Service Center for Visual Sensory Disabilities (PPSDSN) in Kudus Regency. The data consist of words, symbols, and expressions found in religious poems written by individuals with visual sensory disabilities. Data analysis was conducted using heuristic and hermeneutic techniques. The findings reveal that denotative meanings reflect everyday experiences, emotional relationships, and expressions of gratitude. Connotative meanings uncover deeper symbolic interpretations related to faith, resilience, hope, and spiritual dependence. Meanwhile, the myths identified represent broader socio-cultural ideologies, including divine love as a source of strength, the acceptance of limitations, and spirituality as a means of overcoming loneliness and social marginalization. The novelty of this study lies in applying Barthes’ semiotic analysis to disability literature, particularly religious poetry, which remains underexplored. This research contributes to expanding literary studies on disability by highlighting poetry as a medium of spiritual expression and social representation.